Experimental leaching of massive sulphide from TAG active hydrothermal mound and implications for seafloor mining. (January 2018) - Fallon, Emily K.; Niehorster, Ella; Brooker, Richard A.; Scott, Thomas B.
Abstract: Seafloor massive sulphide samples from the Trans-Atlantic Geotraverse active mound on the Mid-Atlantic Ridge were characterised and subjected to leaching experiments to emulate proposed mining processes. Over time, leached Fe is removed from solution by the precipitation of Fe oxy-hydroxides, whereas Cu and Pb leached remained in solution at ppb levels. Results suggest that bulk chemistry is not the main control on leachate concentrations; instead mineralogy and/or galvanic couples between minerals are the driving forces behind the type and concentration of metals that remain in solution. Dissolved concentrations exceed ANZECC toxicity guidelines by 620 times, implying the formation of localised toxicity in a stagnant water column. Moreover, concentrations will be higher when scaled to higher rock-fluid ratios and finer grain sizes proposed for mining scenarios. The distance at which dilution is achieved to meet guidelines is unlikely to be sufficient, indicating a need for the refinement of the mining process. Graphical abstract: Highlights: Metals leached from different samples of a SMS deposit (TAG) vary significantly Cu and Pb are leached and remain in solution within ppb range. Fe oxy-hydroxides present in a deposit have the potential to reduce toxicity. Dissolved concentrations imply localised toxicity in stagnant water column. Risk of higher toxicity with more realistic mining scenarios.